Difference between revisions of "T test diff of mean"
From OPOSSEM
(3 intermediate revisions by 2 users not shown) | |||
Line 1: | Line 1: | ||
− | <math> t = \frac{\bar{y}_2 - \bar{y}_1 | + | <math> t = \frac{\bar{y}_2 - \bar{y}_1}{s_{\bar{y}_2-\bar{y}_1}}</math>, where <math>s_{\bar{y}_2-\bar{y}_1} = \sqrt{\frac{(n_1-1)s_1^2+(n_2-1)s_2^2}{n_1+n_2-2}}\sqrt{{\frac{1}{n_1}}+{\frac{1}{n_2}}}</math> with <math>\text{df} = n_1+n_2-2</math> |
+ | |||
+ | |||
+ | <noinclude>[[Category:Equations]]</noinclude> |
Latest revision as of 13:01, 7 July 2011
<math> t = \frac{\bar{y}_2 - \bar{y}_1}{s_{\bar{y}_2-\bar{y}_1}}</math>, where <math>s_{\bar{y}_2-\bar{y}_1} = \sqrt{\frac{(n_1-1)s_1^2+(n_2-1)s_2^2}{n_1+n_2-2}}\sqrt{{\frac{1}{n_1}}+{\frac{1}{n_2}}}</math> with <math>\text{df} = n_1+n_2-2</math>